Enhancing Language Corner Management with Henry Fayol’s Principles at Darussalam Gontor University - Lalu Abdul Aziz Ramli; Nuril Mufidah; M Syahrul Anwar; Naufal Fikri; Kinanti Ruhamma Furqan (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2023)
The purpose of this study to describe the program of management Languge Corner based on fourteen managements principles of Henry Fayol in the form (Division of Work, Authority and Responsibility, Discipline, Unity of Command, Unity of Direction, Subordination of Individual Interests, Payroll, Centralization, Scalar Chains, Order, Justice, Stability, Initiative, Spirit of Unity). The research approach used in this study is a qualitative descriptive approach with a case study type. The research subjects were at the Educational Institute of Darussalam Gontor University, Ponorogo. Techniques of data collection were collected through observation of Langugage Corner program management and interviews with heads of Arabic language teaching programs and students as well and administrative documentation. Data analysis included data display, data reduction and drawing conclusions. The results showed that the management of the Language corner program at Darussalam Gontor University had used fourteen management principles from Henry Fayol. Each indicator of management principle was included of category highly implemented which means that these fourteen management principles had been implemented in the language corner program. at Darussalam Gontor University. The four of these principles are: prioritizing organizational interests over individual interests, fair compensation, centralization and scalar chain are included in applied criteria.